METHODOLOGY FOR THE FORMATION OF A SYSTEM OF SPIRITUAL AND MORAL VALUES IN PRIMARY SCHOOL STUDENTS - Azimjanov Nazirbek (Journals Park Publishing, 2024)
This article discusses ideas and reflections on the methodology for developing a system of moral and ethical values in primary school students. In a rapidly changing world, nurturing spiritual and moral values in young students has become essential. Schools play a crucial role in shaping students' character, helping them become responsible, ethical, and compassionate individuals. Elementary school serves as the foundation for this development, making it vital to implement a well-structured methodology that promotes these values.
Keywords: primary school students, value formation, spiritual development, educational methodology, character building, ethical education, value system, socialization, teaching strategies.